A Functional Genetic Screen Identifies the Phosphoinositide 3-kinase Pathway as a Determinant of Resistance to Fibroblast Growth Factor Receptor Inhibitors in FGFR Mutant Urothelial Cell Carcinoma - Wang, Liqin; Šuštić, Tonći; Leite de Oliveira, Rodrigo; Lieftink, Cor; Halonen, Pasi; van de Ven, Marieke; Beijersbergen, Roderick L.; van den Heuvel, Michel M.; Bernards, René; van der Heijden, Michiel S. (European urology, 2017)
Activating mutations and translocations of the FGFR3 gene are commonly seen in urothelial cell carcinoma (UCC) of the bladder and urinary tract. Several fibroblast growth factor receptor (FGFR) inhibitors are currently in clinical development and response rates appear promising for advanced UCC. A common problem with targeted therapeutics is intrinsic or acquired resistance of the cancer cells. To find potential drug targets that can act synergistically with FGFR inhibition, we performed a synthetic lethality screen for the FGFR inhibitor AZD4547 using a short hairpin RNA library targeting the human kinome in the UCC cell line RT112 (FGFR3-TACC3 translocation). We identified multiple members of the phosphoinositide 3-kinase (PI3K) pathway and found that inhibition of PIK3CA acts synergistically with FGFR inhibitors. The PI3K inhibitor BKM120 acted synergistically with inhibition of FGFR in multiple UCC and lung cancer cell lines having FGFR mutations. Consistently, we observed an elevated PI3K-protein kinase B pathway activity resulting from epidermal growth factor receptor or Erb-B2 receptor tyrosine kinase 3 reactivation caused by FGFR inhibition as the underlying molecular mechanism of the synergy. Our data show that feedback pathways activated by FGFR inhibition converge on the PI3K pathway. These findings provide a strong rationale to test FGFR inhibitors in combination with PI3K inhibitors in cancers harboring genetic activation of FGFR genes. Fibroblast growth factor receptor (FGFR) inhibitors are tested in bladder cancer patients. A genetic screen identified the phosphoinositide 3-kinase pathway to determine drug resistance. Combined treatment with FGFR and phosphoinositide 3-kinase inhibitors may improve response rates in patients with cancers harboring activating FGFR mutations